Antibacterial Effects of Brown Algae Extract against Tilapia Spoilage Bacteria Pseudomonas fluorescens and Shewanella putrefaciens - Xin Liu; Wenqiao Yuan; Ying Liu (BioResources, 2023)
Inhibitory effects were evaluated for the extract from edible brown algae Ascophyllum nodosum vs. Pseudomonas fluorescens and Shewanella putrefaciens, which are tilapia spoilage organisms. Modified Gompertz and Logistic models were used to describe the inhibition effect of the extract, and both models indicated that the extract could inhibit bacteria growth by extending lag time and reducing maximum growth rate. The Lambert-Pearson model was applied to calculate the minimum inhibitory concentration (MIC) and non-inhibitory concentration (NIC) of the extract. The best-fit MIC and NIC values for P. fluorescens were 1.145 and 0.036 mg/mL, and 0.947 and 0.106 mg/mL for S. putrefaciens, respectively. Bacteriostatic assays on agar plates showed that the extract applied at concentrations higher than the MIC caused significant bacteriostatic effects, especially in S. putrefaciens. Algae extract (42 μg/disc) had inhibition zones against both P. fluorescens (1.72 cm) and S. putrefaciens (1.58 cm) in a disc diffusion assay. Treating tilapia fillets with the extract significantly reduced the total viable counts of both bacterial strains and postponed spoilage odor occurrence time (day 2 for the control group vs. day 9 for the extract treated group) during storage at 4 °C.  These findings suggest that the extract could be used as a natural anti-bacterial and preservation agent to extend the shelf life of cold storage tilapia.